2021
DOI: 10.1097/j.pain.0000000000002236
|View full text |Cite
|
Sign up to set email alerts
|

A Glra3 phosphodeficient mouse mutant establishes the critical role of protein kinase A–dependent phosphorylation and inhibition of glycine receptors in spinal inflammatory hyperalgesia

Abstract: Glycinergic neurons and glycine receptors (GlyRs) exert a critical control over spinal nociception. Prostaglandin E2 (PGE2), a key inflammatory mediator produced in the spinal cord in response to peripheral inflammation, inhibits a certain subtype of GlyRs (α3GlyR) that is defined by the inclusion of α3 subunits and distinctly expressed in the lamina II of the spinal dorsal horn, ie, at the site where most nociceptive nerve fibers terminate. Previous work has shown that the hyperalgesic effect of spinal PGE2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 42 publications
(77 reference statements)
4
21
1
Order By: Relevance
“…In HEK293 cells cotransfected with cDNAs encoding for GlyRα3 and EP2 receptors, application PGE 2 led to a decrease in glycinergic membrane currents with no change in their inactivation kinetics or plasma membrane expression. In single channel recording experiments, activation of PKA progressively reduced single current amplitudes to about 66%, which is close to the inhibition of glycinergic synaptic currents observed in mouse spinal cord slices [5,8,14]. Introducing the phospho-mimicking serine to glutamate (S→E) mutation reduced single channel conductance to a similar degree with no effect on single channel open probabil-ity.…”
Section: Glyrs In Inflammatory Hyperalgesia and Allodyniasupporting
confidence: 61%
See 3 more Smart Citations
“…In HEK293 cells cotransfected with cDNAs encoding for GlyRα3 and EP2 receptors, application PGE 2 led to a decrease in glycinergic membrane currents with no change in their inactivation kinetics or plasma membrane expression. In single channel recording experiments, activation of PKA progressively reduced single current amplitudes to about 66%, which is close to the inhibition of glycinergic synaptic currents observed in mouse spinal cord slices [5,8,14]. Introducing the phospho-mimicking serine to glutamate (S→E) mutation reduced single channel conductance to a similar degree with no effect on single channel open probabil-ity.…”
Section: Glyrs In Inflammatory Hyperalgesia and Allodyniasupporting
confidence: 61%
“…The recent generation of a genetically engineered S346A point mutated mouse line allowed filling this gap (Figure 2). This mouse carries a serine to alanine amino acid exchange at position 346 (S346A mutation) in the PKA consensus sequence of the GlyR α3 subunit [8]. Electrophysiological recordings from substantia gelatinosa neurons in spinal cord slices of these mice demonstrated not only that the point-mutated α3GlyRs were resistant to inhibition by PGE 2 but also confirmed the critical contribution of phosphorylation at this site to inflammatory hyperalgesia.…”
Section: Glyrs In Inflammatory Hyperalgesia and Allodyniamentioning
confidence: 84%
See 2 more Smart Citations
“…Using recombinant expression of mutant GlyRs, Harvey et al (2004) identified the S346 residue within the ICD of α3GlyRs as the residue targeted by PKA. The recent generation of a knock-in mouse line carrying the S346A mutation in the Glra3 gene allowed direct examination of the relevance of this chronic pain mechanism in vivo ( Werynska et al, 2021 ). Behavioral experiments demonstrated that α3GlyR-S346A mice are devoid of pain sensitization elicited by intrathecal PGE 2 and display a diminished inflammatory pain hyperalgesia.…”
Section: Glycine Receptor Subtypes Involved In Nociception and Chroni...mentioning
confidence: 99%